Pengalaman Anak Usia 5-6 Tahun dalam Penerapan Metode Drill dalam Mengenal Shalat di TK IT Robbani Desa Ujung Batu I - Siti Khodijah Nst; Rustam Rustam; Ahmad Syukri Sitorus (Institut Nalanda, 2025)
This research aims to find out what children's experiences are during the preparation stage before learning to pray using the drill method at the IT Robbani Kindergarten, and what the children's experiences are during learning to pray using the drill method at the IT Robbani Kindergarten. The research method in this thesis uses descriptive qualitative research. The subjects in this research were the teachers and students of the IT Robbani Kindergarten. The data collection technique process uses interviews, observation and documentation. The data analysis technique in this research uses the Miles & Huberman interactive data analysis model. There are three streams of activities which simultaneously reduce data, present data, formulate conclusions, and verify data analysis. The results of research at the IT Robbani Kindergarten show that children's experiences at the preparation stage are: apperception, conveying goals, and providing motivation. It has been implemented well, using the question and answer method and lectures in a persuasive tone, and motivating children by reading hadith and connecting emotionally with their parents. This experience is carried out by repeating movements and readings in prayer every day.